2009
DOI: 10.12693/aphyspola.116.655
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Mode Distribution and Steady State Distribution in Step-Index Glass Optical Fibers

Abstract: Using the power flow equation, we have examined mode coupling in a step-index multimode glass optical fiber. As a result, the coupling length at which the equilibrium mode distribution is achieved and the length of fiber required for achieving the steady-state mode distribution are obtained. These lengths are much longer for glass fiber than they are for plastic optical fibers. Our results are in good agreement with experimental results reported earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[17][18][19][20][21] With the modes redistributed, each mode group gradually reaches an equilibrium state. [22][23][24][25][26][27][28] The transmission bandwidth can be improved by transmitting the equilibrium state mode, with good transmission characteristics. However, there has been no report on the bandwidth and transmission characteristics with regard to mode controllers except in one study, 29) wherein only a preliminary result of the eye pattern was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] With the modes redistributed, each mode group gradually reaches an equilibrium state. [22][23][24][25][26][27][28] The transmission bandwidth can be improved by transmitting the equilibrium state mode, with good transmission characteristics. However, there has been no report on the bandwidth and transmission characteristics with regard to mode controllers except in one study, 29) wherein only a preliminary result of the eye pattern was reported.…”
Section: Introductionmentioning
confidence: 99%